Pembuatan Edible Film Berbasis Tapioka dengan Penambahan Gelatin dan Aplikasinya pada Kemasan Permen Komersial - Afiifah Kaltsum; Umar Kalmar Nizar; Desy Kurniawati (Lembaga Yasin AlSys, 2026)
Commercial candies are generally packaged using conventional plastics that are difficult to degrade and may cause chemical compounds to migrate into food products. Meanwhile, tapioca has the potential to be developed as a raw material for edible films but is limited by its hydrophilic properties and low mechanical strength. This study aimed to produce a tapioca-based edible film with gelatin added as a structural reinforcement and to evaluate its physical and functional characteristics for commercial candy packaging applications. The edible film was produced by gelatinizing 5 g of tapioca in 100 mL of distilled water with the addition of 7.5 mL of glycerol and gelatin at concentrations of 1%, 2%, and 3% for formulations F1, F2, and F3, respectively, along with a control formulation without gelatin. The films were then cast and dried at 60 °C for 24 h. Characterization included testing moisture content, biodegradability through a seven-day soil burial test, swelling capacity, and functional groups using FTIR spectroscopy. The results showed that the moisture content increased with increasing gelatin concentration, ranging from 11.9% to 15.5%, and all formulations met the maximum threshold of 16% stipulated in SNI 06-3735-1995. The highest biodegradability was obtained for F3 at 81%, exceeding the threshold of more than 60% stipulated in SNI 7188.7:2016. Water absorption capacity also increased with increasing gelatin concentration, from 47.2% in the control formulation to 74.0% in F3. The FTIR spectra revealed amide I bands at 1643–1646 cm⁻¹ and amide II bands at 1542–1543 cm⁻¹ in all gelatin-containing samples, confirming the successful incorporation of gelatin into the tapioca matrix without disrupting the glycosidic bonds of starch. These findings indicate that the formulation containing 3% gelatin exhibited the highest biodegradability, although it also produced the greatest water absorption capacity. Overall, tapioca–gelatin-based edible films have the potential to be developed as a biodegradable alternative for candy packaging to support the reduction of plastic waste in small- and medium-scale food industries.